Dental Caries in Twelve- and Fifteen-Year-Olds: Results from the Basic Oral Health Survey in Haiti - Walter J. Psoter, DDS, PhD; H. Ludwig P. Saint Jean, DDS, MPH; Douglas E. Morse, DDS, Ph.D; (Blackwell Synergy, 2005)
Reports on oral health investigations in Haiti are sparse. There are only three peer-reviewed published articles on oral health in Haiti. In order to construct a national dataset useful for public health planning, a representative dental caries survey of Haitian school attending children was onducted in 1999.